Kerentanan Perbankan di Indonesia: Pengukuran dan Penyebabnya - Wibowo, Wisnu; Zakaria, Amir Ambyah (UI Scholars Hub, 2021)
This study aims to identify banking vulnerabilities and analyze the factors that influence them. The tool used to identify bank vulnerabilities uses modification crisis and default index (C&D Index) while hypothesis testing uses logit regression. Commercial banks in Indonesia from 2008 to 2018 was taken as sample. As a result, in 2008 and 2013 were the most vulnerable conditions for banks in Indonesia. The reason most banks have been identified as vulnerable is due to decreased profits, increased liabilities in foreign currencies and increased Non Performing Loan (NPL). Logit regression test show that banking fragility is negatively related to capital, liquid assets, and financial assets.